Response of Dividend Announcement on the Price of Mutual Fund: A Comprehensive Study on Mutual Fund Listed in Dhaka Stock Exchange (DSE) - Golder, Uttam; Akter, Shahanaz; Sheikh, Md. Imran (International Journal of Scientific Research and Management (IJSRM), 2019)
How dividend policy shakes the price of share of an enterprise` is one of the most significant research issues in the ground of modern investment and finance. This study examines the influence of dividend announcement on the price of the mutual fund those are registered in Dhaka Stock Exchange (DSE). The empirical part of this study uses “event study methodology” to know whether dividend announcement delivers any price sensitive information which creates a movement of the price of mutual funds. Although much studies are made on the topics of dividend policy, it is vague that whether dividend policy effects the stock price. The researcher who supports dividend irrelevance theory, argues that firm’s value should depend on earning power of the company, not on in which way the total earnings are divided into dividend and retained earnings and at what amount dividend are given to the shareholder of the company. This research surveys price of mutual funds those are registered in Dhaka Stock Exchange (DSE) surrounding 44 days of the dividend announcement date. In this study, we examine 13 samples & used event study technique that shows dividend announcement doesn’t convey any price sensitive information immediately after announcement of dividend but price of the mutual fund goes to change dramatically before 7 days of record date which proves that announcement of dividend affects the price of mutual fund registered in Dhaka Stock Exchange (DSE). Finally, T-test also postulates that price of stock responses to dividend announcement is not statistically significant immediately from dividend announcement date to 7 days after the announcement date. However, an opposite result, the T test identifies that price of stock responses to the announcement of dividend is statistically significant from the 7 days before record date to record date.